2018
DOI: 10.1007/s11126-018-9604-5
|View full text |Cite
|
Sign up to set email alerts
|

In Their Own Words: Clinician Experiences and Challenges in Administering Evidence-Based Treatments for PTSD in the Veterans Health Administration

Abstract: The aim of the present study was to increase the understanding of clinician experiences with administering two evidence-based psychotherapies (EBPs) for PTSD (Cognitive Processing Therapy and Prolonged Exposure therapy) in the Veterans Affairs Healthcare System (VA). The study assessed clinician perceptions through the use of two, one-hour focus groups and employed a rigorous data analysis approach, Consensual Qualitative Research. Clinicians who work in an outpatient PTSD clinic at a New England VA, and who r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…However, numerous demographic and military characteristics (e.g., gender, officer rank) were found to influence CPT/PE initiation and timing in this sample. While provider studies (Doran et al, 2019;Osei-Bonsu et al, 2017;Sayer et al, 2017) and the CPT/PE treatment manuals (Foa et al, 2007;Resick et al, 2017) have not reported that demographic and military characteristics influence decision making, this finding is consistent with some previous investigations of CPT/PE initiation (Bovin et al, 2018;Keller & Tuerk, 2016;Shiner et al, 2018;Sripada et al, 2018). Demographics (e.g., age, gender, race/ethnicity) may be associated with symptom presentation and/or severity, potentially influencing decisions to initiate CPT/PE (Koo, Hebenstreit, Madden, & Maguen, 2016;Magruder et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, numerous demographic and military characteristics (e.g., gender, officer rank) were found to influence CPT/PE initiation and timing in this sample. While provider studies (Doran et al, 2019;Osei-Bonsu et al, 2017;Sayer et al, 2017) and the CPT/PE treatment manuals (Foa et al, 2007;Resick et al, 2017) have not reported that demographic and military characteristics influence decision making, this finding is consistent with some previous investigations of CPT/PE initiation (Bovin et al, 2018;Keller & Tuerk, 2016;Shiner et al, 2018;Sripada et al, 2018). Demographics (e.g., age, gender, race/ethnicity) may be associated with symptom presentation and/or severity, potentially influencing decisions to initiate CPT/PE (Koo, Hebenstreit, Madden, & Maguen, 2016;Magruder et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The CPT manual recommends one to three information-gathering sessions prior to initiating CPT (Resick et al, 2017), and the PE manual recommends a thorough assessment and building a solid foundation before beginning PE (Foa et al, 2007). Readiness may also refer to the need for psychotherapy prior to CPT/PE initiation, including development of coping/distress tolerance skills (Lu, Plagge, Marsiglio, & Dobscha, 2016; Osei-Bonsu et al, 2017; Sayer et al, 2017; Zubkoff, Carpenter-Song, Shiner, Ronconi, & Watts, 2016) or building a sufficient therapeutic alliance (Doran, O’Shea, & Harpaz-Rotem, 2019; Lu et al, 2016; Osei-Bonsu et al, 2017; Sayer et al, 2017). Veterans echo this rationale, reporting concern about their ability to tolerate CPT/PE and lack of familiarity with their providers as reasons to delay or never initiate CPT/PE (Hundt et al, 2018; Lu et al, 2016; Stecker, Shiner, Watts, Jones, & Conner, 2013).…”
mentioning
confidence: 99%
“…In DSM–5 this heterogeneity has increased by a factor of eight compared with DSM–IV–TR (APA, 2000) as a result of expanded diagnostic criteria of PTSD (Galatzer-Levy & Bryant, 2013). Qualitative studies in PTSD treatment settings consistently identify concerns among providers that there are complex presentations of PTSD that may be a poor fit for the time-limited, structured nature of TF-EBPs (Doran et al, 2019; Lu et al, 2016). Heterogeneity and complexity of presentations may help to explain low engagement and high dropout from TF-EBPs, particularly in the absence of treatment to address emotional dysregulation and treatment-interfering behaviors (Landes et al, 2013).…”
mentioning
confidence: 99%
“…While not an explicit study of treatment adherence, Doran and colleagues (Doran, 2019), interviewed veterans who participated in TFTs for PTSD. Eight had dropped out of treatment and were analyzed separately.…”
mentioning
confidence: 99%